Pengetahuan Orang Tua Tentang Karies Gigi Pada Anak Pra Sekolah TK Gotong Royong Surabaya Tahun 2023 - Ratri Dian Pratiwi; Isnanto; Sri Hidayati (SURABAYA DENTAL THERAPIST JOURNAL, 2024)
Background: Dental caries is a disease that damages tooth tissues: enamel, dentin, and pulp structures. Children often suffer from tooth decay, which can interfere with their daily lives. Research topic: Average height of Gotong Royong kindergarten in Surabaya in 2022. Survey method: Application of descriptive research. The subjects of this study were a total of 49 parents of PAUD children attending Surabaya Gotong Royong Kindergarten. The data collection method is the answer to the questionnaire. The data analysis technique used is to provide the proportion of responses for each category of data and display it in tabular form. Research result: Parental knowledge of the definition of caries in preschool children fell into the 'good' category (72%), while parental knowledge of the causes of caries in preschool children fell into the 'good' category (81%). It is known that , parental knowledge of the causes of tooth decay in preschool children falls into the 'good' category (81%). Knowledge of the effects of caries in preschool children falls into the category of 'good' (77%), and parental knowledge of caries prevention in preschool children is adequate. Parents' knowledge of caries care in preschool children is in the 'good' (70%) and 'good' (87%) categories. Conclusion: Based on this study, it can be concluded that the parents' knowledge of tooth decay in the preschoolers of Gotong Royong Surabaya Kindergarten is in the good category.